The Influence Of Sowing Dates And Norms On Technological Quality Indicators Of Rice Grain - Urazmetov K.K; Jobberganov A.K; Akhmad Kurbonov (Zien Journals, 2022)
As a result of the experiment, it was found that the technical quality indicators of rice varieties are 3.6-4.5% higher than the control. When comparing the varieties, it was observed that the technical quality indicators of the Tarona variety were higher. As a result of the observations, it was found that the earlier the plant is planted and completes the vegetation period, the more heat and light it absorbs into its body, the higher the vitreousness of rice.
Keywords: rice; sowing date; spikes; stems